Case Report: FIA plus venetoclax in a patient on hemodialysis - Herstein, Jacob E.; Marx, Kayleigh R.; Savoy, J. Michael; Jen, Wei Ying; Yilmaz, Musa; Short, Nicholas J.; Issa, Ghayas C.; Ravandi, Farhad; Kadia, Tapan M.; Daver, Naval G.; DiNardo, Courtney D. (Frontiers in Oncology, 2026)
The safe and effective delivery of curative cytotoxic chemotherapy for acute myeloid leukemia (AML) in patients receiving intermittent hemodialysis (IHD) for end-stage renal disease (ESRD) remains a clinical challenge; pharmacological and logistical barriers necessitate close interdisciplinary coordination. In this case, we report a 65-year-old female patient with chronic ESRD on IHD and newly diagnosed AML who achieved complete remission (CR) after treatment with fludarabine, idarubicin, and cytarabine plus venetoclax (i.e., FIA + venetoclax).